Dignity of Older Persons With Mental Health Conditions: Why Should Clinicians Care? - Banerjee, Debanjan; Rabheru, Kiran; Ivbijaro, Gabriel; Mendonca Lima, Carlos Augusto de (Frontiers in Psychiatry, 2021)
With a steady increase in population aging, the proportion of older people living with mental illness is on rise. This has a significant impact on their autonomy, rights, quality of life and functionality. The biomedical approach to mental healthcare has undergone a paradigm shift over the recent years to become more inclusive and rights-based. Dignity comprises of independence, social inclusion, justice, equality, respect and recognition of one's identity. It has both subjective and objective components and influences life-satisfaction, treatment response as well as compliance. The multi-dimensional framework of dignity forms the central anchor to person-centered mental healthcare for older adults. Mental health professionals are uniquely positioned to incorporate the strategies to promote dignity in their clinical care and research as well as advocate for related social/health policies based on a human rights approach. However, notwithstanding the growing body of research on the neurobiology of aging and old age mental health disorders, dignity-based mental healthcare is considered to be an abstract and hypothetical identity, often neglected in clinical practice. In this paper, we highlight the various components of dignity in older people, the impact of ageism and mental health interventions based on dignity, rights, respect, and equality (including dignity therapy). It hopes to serve as a framework for clinicians to incorporate dignity as a principle in mental health service delivery and research related to older people.